WACANA TOLERANSI DALAM PROGRAM “KAMPUNG MODERASI BERAGAMA” KABUPATEN BANGKA TENGAH - Pricispa, Izcha; Harahap, Fitri Ramdhani; Herza, Herza (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2025)
Indonesia's multicultural society, especially about religious diversity, has the potential for inter-religious conflict. In this regard, the Ministry of Religious Affairs of the Republic of Indonesia, as the representation of the state, designed a religious moderation village program. The purpose of the program is to overcome religious issues that have the potential for religious conflict, such as: intolerance, radicalism, or even violence stemming from various religious differences that exist. This research aims to analyze the discourse of tolerance that is constructed in the religious moderation village program in Central Bangka. Second, to analyze the production of tolerance discourse and the interpretation of the people of Central Bangka. Third, to analyze the socio-political context that influences the formation of tolerance discourse in the religious moderation village program in Central Bangka. The research was conducted in Central Bangka. This research uses a qualitative approach with a critical discourse analysis method. The technique of determining research informants using purposive sampling with data collection techniques of interviews, observation, and documentation. The results of this study show that the discourse of tolerance constructed at the text analysis level uses language that is easily accepted by the community. In addition, the production process of tolerance discourse is carried out by actors who have social and political power and interpretations from the community related to this program are also not always linear with policy agencies, although most people accept the narrative of moderation and tolerance. Finally, situational, institutional, and social are interrelated. Starting from the issue of intolerance in Central Bangka to the influence of organizational institutions in the production of tolerance discourse and the political system in Central Bangka.